ANALISIS SANITASI LINGKUNGAN DAN PERILAKU PENJAMAH MAKANAN TERHADAP KEPADATAN KECOAK DI KANTIN PELABUHAN DUMAI - Dwi Yanti Tanjung; Agrina Agrina; Ridwan Manda Putra (Jurnal Ilmu Lingkungan, 2020)
The research objective was to analyze the environmental sanitation and behavior of food handlers with the vector density of cockroaches in the Dumai Port canteen. It is an observational research with cross sectional method and quantitative data type. The research location was at the Port of Dumai canteen with the first population, namely 24 canteens, total sampling technique, the second 48 food handlers and the third population of 78 buyers with purposive sampling. Relationship analysis was performed using multiple linear regression. With the results of environmental sanitation that meet the health requirements of 20.83% and do not meet the health requirements of 79.17% and the behavior of food handlers as many as 8 (16.67%) have bad behavior, 17 (35.42%) have good enough behavior and 23 (47.91%) good behavior, 6 canteens in medium category and 18 high category canteens. The results of the analysis showed a strong (r = 0.799) and significant (p value = 0.000) relationship between environmental sanitation and cockroach density and a very weak correlation (r = 0.015) between food handler behavior and cockroach density in the Dumai Port canteen (pvalue = 0.946) greater than 0.05 means that there is no relationship between food handler behavior and cockroach density. The economic factor of the price and location purchasing decisions becomes the consumer decision-making process in buying at the Dumai Port Canteen. The suggestion in this research is the need to improve environmental sanitation and increase the supervision of port health workers to reduce the cockroach population in the Dumai Port Canteen.